2017
DOI: 10.1097/md.0000000000008070
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality-of-life assessment in surgical patients with papillary thyroid carcinoma

Abstract: Even with a favorable prognosis, the health-related quality of life (HRQoL) of papillary thyroid carcinoma (PTC) patients remains unclear and conflicting. Thus, in the present study, we compared the HRQoL of PTC patients with that of the general population (GP).The study was performed in our thyroid and parathyroid surgery department, and 186 PTC patients who had undergone thyroidectomy were included. The exclusion criteria were an age < 18 years, no follow-up, and the presence of other malignant neoplasms. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
4
19
0
Order By: Relevance
“…In one study, HRQoL is measured both preoperatively and during two years of follow-up. Although HRQoL increases during follow-up, it does not reach the same level as the general population 179 . In another study HRQoL is measured pre-operatively and during a one-year follow-up, and according to these results HRQoL return to baseline values 180 .…”
Section: Hrqol In Thyroid Cancer Survivorsmentioning
confidence: 76%
“…In one study, HRQoL is measured both preoperatively and during two years of follow-up. Although HRQoL increases during follow-up, it does not reach the same level as the general population 179 . In another study HRQoL is measured pre-operatively and during a one-year follow-up, and according to these results HRQoL return to baseline values 180 .…”
Section: Hrqol In Thyroid Cancer Survivorsmentioning
confidence: 76%
“…Lubitz et al showed a temporary decrease of QoL after initial therapy, but after 6 months QoL was comparable to baseline (21); it must be noted that only half of their population received RAI therapy, and the majority of these patients received RAI therapy after preparation with rhTSH. Gou et al (17) and Ryu et al (19) showed a decreased QoL after initial therapy which thereafter increased again, but was still below baseline at the end of follow-up. Ryu et al had a follow-up of just 12 months so nothing was known about QoL evolution thereafter (19), while Gou et al followed during 24 months thyroid cancer patients who did not received RAI therapy (17).…”
Section: Discussionmentioning
confidence: 91%
“…Main drawback of the aforementioned cross-sectional studies is that no conclusions can be drawn about QoL evolution over time. Therefore, more recently several longitudinal studies were conducted (16,17,19,20,21). Their results were mixed as some showed increasing QoL (16,20), and others showed decreasing QoL over time (17,19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis performed by Gressier et al showed that the SS genotype was associated with post-traumatic stress disorder in subjects exposed to severe trauma [47]. The mortality caused by PTC is low, patients must observe after surgery to prevent any recurrence, and long-term tightness may lead to psychological problems [48]. An important finding of our study was that the 5-HTTLPR SS genotype was associated with PTSD and led to poor clinical outcomes and results in patients with PTC.…”
Section: Post-traumatic Stress Disorder In Patients With Thyroid Cancermentioning
confidence: 99%